The Effect of Social Media Marketing Programs in the Online Retail Industry on Purchase of Sporting Goods - Hossein Norouzi; Fatemeh Darvish; Mohammad Mesbahi (Sports Business Journal, 2021)
Purpose: The current study investigates the effect of social media marketing programs on brand attitudes and consumers' purchase intention of sporting goods in the online retail industry. The case study of this research is Anik online shop.Methodology: A researcher-made questionnaire was designed in this research distributed to the research sample after verifying content validity and structure and its reliability. The statistical population in this research includes members of at least one of the Anik brand social media. Data collection was performed by selecting 559 people using a simple nonprobability sampling method. Structural equation modelling was used in the SPSS and LISREL software.Findings: Results showed that all six research hypotheses are acceptable at a 95% confidence level. The study results showed that the social media marketing program has a significant impact on the retail industry of sports products by influencing consumers' attitudes toward the brand and their shopping tendencies.Originality: Few studies have been done on the social media sports retail industry. Thus, the research results showed us consumers' attitudes toward the brand and their purchasing plans on these platforms.